DFT and Molecular Docking Study of 2-[2-(4-Chlorophenylaminothiazol-5-yl]benzothiazole - Femila Nirmal, N.S.; Fen Reji, T.F. Abbs (Asian Journal of Chemistry, 2019)
The title compound was computed by means of DFT chemical quantum calculations to obtain optimized molecular geometry, harmonic vibrational frequencies and atomic charges. Vibrational bands to the various structural groups and their importance were predicted by analyzing the vibrational spectra. The data showed that B3LYP method provide satisfactory data for assigning vibrational frequencies and structural properties.The HOMO and LUMO energies calculated permit the determination of atomic and molecular parameters and they also represented the transfer of charge in the molecule. Mulliken atomic charge analysis was also done. A comprehensive molecular picture of 2-[2-(4-chlorophenylaminothiazol-5-yl]benzothiazole and its interactions were got from NBO investigations. The molecular docking study indicates that benzothiazole derivative may possess inhibitory activity against BCL2 pancreatic cancer cell lines.